Designing and standardizing a test to measure the accuracy of long-range shooting from knee level for handball players aged (15-17) years - fathi, Moushriq (Journal of Physical Education, 2024)
The researcher noticed a clear weakness in the emerging players in the skill of shooting from the knee level, so he required a way to measure it scientifically through work to evaluate them and the lack of libraries to test this skill for the purpose of discovering the best level of the three levels of the target (upper, middle or lower) that is easier to reach. The study represents a twofold objective, the first of which is to design and build a test to measure the accuracy of the accuracy of shooting with the fulcrum leg from the level of the knees for handball backline players, and the second is the technicalities of this test, and the human field was represented by players of the specialized schools of the Handball Federation with ages (15 - 17 years). old, and the time was: From 4-3-2023 to 5-5-2023, and the spatial domain is the sports halls of these centers in Baghdad and the governorates, and the descriptive method used the survey method and research formed from 12 schools affiliated with these centers in Baghdad and the governorates, and the descriptive method used the survey method and research damage from 12 schools affiliated with these centers in Baghdad and the governorates, and the descriptive method used the survey method and research formed from 12 schools affiliated with these centers in Baghdad and the governorates, and the descriptive method used the survey method and research formed from 12 schools affiliated with these centers in Baghdad and the governorates The research sample consisted of 140 players and the researcher concluded that the test that was designed and standardized can measure this skill properly, the test tool designed by the Author performed its effect perfectly, and recommended the necessity of using this test and the possibility of applying it to handball players in the future, and the test that was standardized can be developed, modified and applied to other ages both genders.